Indigenous Language Broadcasting in Ghana: Retrospect and Prospect - Akpojivi, Ufuoma; Fosu, Modestus (Springer link (Palgrave Macmillan, London), 2016)
This chapter discusses indigenous radio broadcasting in Ghana with the focus on the role played by indigenous languages in empowering various social groups in the society within the democratic arrangement of the country. This contribution is an attempt to awaken research interest in various aspects of indigenous broadcasting in Ghana and other emerging democracies with similar socio-political and media developments. A literature search shows few studies that have examined the role or place of indigenous languages in the media and political democratisation process in emerging democracies like Ghana or Africa as a whole. While most studies are either focused on the positive developments that have characterised emerging democracies following the embrace of deregulation, the few available studies on the use of local language in the media are mainly from East European and Asian perspectives (Blankson, 2005). The deregulation of the broadcasting sphere in Ghana during the late 1990s and the various policies that were formulated later to make broadcasting beneficial not only to media organisations but also to the various sections of society make an evaluation of some aspects of the enterprise worthwhile.
Book Chapter
Keywords: Local Language; Radio Station; Minority Language; Indigenous Language; Dominant Language